A note to transfer pricing audit performance by Indonesia’s tax administration based on tax court decision 2015-2019 on manufacturing industry - Maria R.U.D. Tambunan (Jurnal Akuntansi dan Auditing Indonesia)
This research discusses the transfer pricing audit performance of Directorate General of Taxes (DGT) based on the tax court stipulation during fiscal year 2015-2019. This research employed qualitative research method. The data were collected through literature review and interview. The findings showed that the cases brought to the tax court solely due to administrative and technical matters had been quite significant in number, which were more than 40% of the cases settled. Unfortunately, inappropriate assessment process took the larger proportion in the failure in complying with the technical and administrative rules while conducting the audits. On the other hand, in regards with non-technical and administrative issues, DGT mostly won the cases. It means that DGT were more reliable in auditing once it complied with the technical and administrative matters. The research also showed that DGT fully realized that the infrastructure of transfer pricing handling needed supports from various aspects.